Experimental method of measuring coefficient of transmission capacity and energy storage building a wall - PRODJINONTO, Vincent; DANGBEDJI, Célestin; AWANTO, CHRISTOPHE; VIANOU, COKOU ANTOINE (My University, 2013)
Currently, a new revolution is taking place in the construction of habitus in Europe, respect for nature, ensuring comfort and less energy. In this context, different software currently on the market, offering, for given climatic conditions, the composition of the walls of the building to ensure a transmission inertia, but inertia absorption. But so far, there is no method for measuring coefficient of transmission and storage of in-situ construction, to confirm or refute the data from artificial stones. This work raises this obstacle by developing a simple easy to implement and inexpensive method.
Keywords: Coefficient of transmission; storage capacity; inertia transmission; absorption inertia.